Optical redox ratio using endogenous fluorescence to assess the metabolic changes associated with treatment response of bioconjugated gold nanoparticles in streptozotocin-induced diabetic rats. (25th April 2017) - Adavallan, K; Gurushankar, K; Nazeer, Shaiju S; Gohulkumar, M; Jayasree, Ramapurath S; Krishnakumar, N
Abstract: Fluorescence spectroscopic techniques have the potential to assess the metabolic changes during disease development and evaluation of treatment response in a non-invasive and label-free manner. The present study aims to evaluate the effect of mulberry-mediated gold nanoparticles (MAuNPs) in comparison with mulberry leaf extract alone (MLE) for monitoring endogenous fluorophores and to quantify the metabolic changes associated with mitochondrial redox states during streptozotocin-induced diabetic liver tissues using fluorescence spectroscopy. Two mitochondrial metabolic coenzymes, reduced nicotinamide dinucleotide (NADH) and oxidized flavin adenine dinucleotide (FAD) are autofluorescent and are important optical biomarkers to estimate the redox state of a cell. Significant differences in the autofluorescence spectral signatures between the control and the experimental diabetic animals have been noticed under the excitation wavelength at 320 nm with emission ranging from 350–550 nm. A direct correlation between the progression of diabetes and the levels of collagen and optical redox ratio was observed. The results revealed that a significant increase in the emission of collagen in diabetic liver tissues as compared with the control liver tissues. Moreover, there was a significant decrease in the optical redox ratio (FAD/(FAD + NADH)) observed in diabetic control liver tissues, which indicates an increased oxidative stress compared to the liver tissues of control rats. Further, the extent of increased oxidative stress was confirmed by the reduced levels of reduced glutathione (GSH) in diabetic liver tissues. On a comparative basis, treatment with MAuNPs was found to be more effective than MLE for reducing the progression of diabetes and improving the optical redox ratio to a near normal range in streptozotocin-induced diabetic liver tissues. Furthermore, principal component analysis followed by linear discriminant analysis (PC-LDA) has been used to classify the autofluorescence emission spectra from the control and the experimental group of diabetic rats. The results of this study raise the important possibility that fluorescence spectroscopy in conjunction with multivariate statistical analysis has tremendous potential for monitoring or potentially predicting responses to therapy.